The Dopamine Transporter: Comparative Ultrastructure of Dopaminergic Axons in Limbic and Motor Compartments of the Nucleus Accumbens - Nirenberg, Melissa J. (J Neurosci, 1997)
The dopamine transporter (DAT) regulates extracellular dopamine concentrations, transports neurotoxins, and acts as a substrate for cocaine reinforcement. These functions are known to differ in the limbic-associated shell and motor-associated core compartments of the nucleus accumbens (NAc). Previous studies have shown differential expression of DAT in the NAc shell and core but were limited in resolution to the regional level. Thus, it is not known whether there are differences in the amount, subcellular localization, or plasmalemmal targeting of DAT within individual dopaminergic axons in the two regions. We used high-resolution electron microscopic immunocytochemistry to investigate these possibilities. We show that in both the shell and core, DAT immunogold labeling is present in tyrosine hydroxylase-immunoreactive varicose axons that form symmetric synapses. Within these labeled axons, most DAT gold particles are located on extrasynaptic plasma membranes, but some are associated with intracellular membranes. Dopaminergic axons in the shell contain lower mean densities of both total DAT gold particles (per square micron) and plasmalemmal DAT gold particles (per micron) than those in the core. Within labeled axons in the NAc shell and core, however, there are no detectable differences in the subcellullar distribution of DAT or the percentage of total DAT gold particles that are located on plasma membranes. These studies are the first to examine and compare the subcellular localization of DAT in the NAc shell and core. As a result, they identify intrinsic, cell-specific differences in the expression of DAT within dopaminergic axons in these functionally distinct striatal compartments.